Product Quality Planning in Laser Metal Processing Based on Open Innovation Using Quality Function Deployment - Nelli Vladimirovna Syreyshchikova; Danil Yurievich Pimenov; Elena Nikolaevna Yaroslavova; Munish Kumar Gupta; Shubham Sharma; Khaled Giasin (Journal of Open Innovation: Technology, Market and Complexity, 2021)
ABSTRACT: The results of the development of a modified quality function deployment (QFD) method, obtained for the first time to improve the product quality planning process in the metal cutting of laser technologies confirming the dynamics of open innovation, are presented. When using new marketing technologies, the requirements of consumers are established; a factorial model of customer satisfaction was determined with after an assessment by expert methods, their wishes were transformed into indicators of product quality, and its concept was developed. Product quality is enhanced by optimizing project specifications. The method of functional cost analysis (FCA) was applied for the manufacturing processes, which made it possible to reduce the costs of their implementation. New methods of product quality control were applied. The developed planning process is described by a sequence diagram, an algorithm, and a responsibility matrix. The research used search methods including Internet resources required for open innovation, namely functional modeling methods (IDEF) and the method of advanced product quality planning (APQP). The results of the achieved advantages of open innovation (reduction in research and development costs, implementation of the principles of total quality management (TQM), customer orientation, process approach, improvement) are recommended for further application both at the enterprise and in the metalworking of mechanical engineering. The practical significance of the results of this work is the reduction in internal and external failures by 12%; reduction in time for new product development by 9%; reduction in costs for online resources by 11% and quality control during production by 7%; reduction in labor costs for process management by 25%; and the stability of the process, which improved by 25%.